Ketrampilan Seni Rupa Dua Dimensi (2D) Membuat Kolase Dari Biji- Bijian Untuk Anak Sd - Sri Putrianingsih (LPPM IAI Hasanuddin Pare-Kediri, 2025)
We often encounter 2-dimensional works of art in everyday life. Where fine art itself is a branch of art that creates a work by using media that can be seen by the sense of sight and also felt by the sense of touch. Collage is a very beautiful type of drawing art. By using high imagination, in the end you will produce many amazing works. One branch of drawing activities is collage. In general, someone will then draw by making a sketch, namely using a pencil, then coloring it using dye.